2020
DOI: 10.34117/bjdv6n9-207
|View full text |Cite
|
Sign up to set email alerts
|

A Fotobiomodulação No Processo Cicatricial Da Pele - Revisão Da Literatura / Photobiomodulation in Wound Healing Process - Literature Review

Abstract: respostas anti-inflamatória e analgésica, sendo outra característica o potencial bioestimulante que ocorre nas células, proporcionando uma cicatrização mais rápida. Embora a aplicação do LBI seja de simples execução, há necessidade de avaliar a especificidade dos parâmetros, uma vez que, durante o protocolo de tratamento, cada um deles é essencial para alcançar o efeito desejado. Cromóforos são moléculas com afinidade pela luz, encontram-se nas mitocôndrias que, ao entrar em ontato com o LBI, geram aumento do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
4
0
3
Order By: Relevance
“… 26 This action results from the modulation of the immune system, decreases the production and release of inflammation mediators, increases the production of mitochondrial adenosine triphosphate, thus decreasing cellular oxidative stress and apoptosis, and stimulates neovascularization. 53 , 54 , 55 , 56 The efficacy results of this study corroborated the efficacy observed in previous preclinical studies in animals that were experimentally subjected to Bothrops venom. 28 , 40 , 57 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 26 This action results from the modulation of the immune system, decreases the production and release of inflammation mediators, increases the production of mitochondrial adenosine triphosphate, thus decreasing cellular oxidative stress and apoptosis, and stimulates neovascularization. 53 , 54 , 55 , 56 The efficacy results of this study corroborated the efficacy observed in previous preclinical studies in animals that were experimentally subjected to Bothrops venom. 28 , 40 , 57 …”
Section: Discussionsupporting
confidence: 87%
“…There is evidence that LLLT improves blood flow, which increases the reabsorption of edema and the clearance of catabolites derived from the inflammatory process, as well as providing an efficient supply of nutritional and defensive elements to the injured region . This action results from the modulation of the immune system, decreases the production and release of inflammation mediators, increases the production of mitochondrial adenosine triphosphate, thus decreasing cellular oxidative stress and apoptosis, and stimulates neovascularization . The efficacy results of this study corroborated the efficacy observed in previous preclinical studies in animals that were experimentally subjected to Bothrops venom …”
Section: Discussionsupporting
confidence: 84%
“…Low-level laser PBM is emerging as an alternative to the use of drugs. PBM with low-level laser has photochemical, photophysical, and photobiological mechanisms, particularly via cytochrome C oxidase, a terminal enzyme in the mitochondrial electron transport chain that causes changes in the biological system by increasing adenosine triphosphate (ATP) production 17 , 18 . In our study, it is believed that mitochondrial pathways are stimulated after PBM, which is related to the increase in iNOS expression in synovial cells.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the increase in ATP, the cells undergo biostimulation, promoting possible therapeutic effects such as morphodifferentiation and cell proliferation, tissue neoformation, increased local microcirculation through angiogenesis, anti-inflammatory and analgesic potential 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory phase aims to remove devitalized tissues, the proliferative phase focuses on tissue formation through fibroblast proliferation and collagen production, and the maturation phase involves collagen type replacement, lasting from 6 months to 2 years. Complications can affect scar characteristics [3][4][5][6][7]. Recognizing the vital importance of biodiversity, the international community has established the Sustainable Development Goals (SDGs), including SDG 15, which aims to protect, restore, and promote the sustainable use of terrestrial ecosystems [8,9].…”
Section: Introductionmentioning
confidence: 99%